Policy and legislative responses to climate change impacts on indigenous medicinal plant resources in South Africa. A desktop-based qualitative policy analysis. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2026)
Background Indigenous medicinal plants play a critical role in South Africa’s primary healthcare systems, cultural heritage, and biodiversity economy. Climate change poses increasing threats to these resources through altered rainfall patterns, rising temperatures, habitat loss, and increased pressure on harvesting. While South Africa has developed progressive environmental and biodiversity legislation, the extent to which existing policy and legal frameworks respond adequately to climate change impacts on indigenous medicinal plant resources remains insufficiently explored. Methods A desktop-based qualitative policy analysis was conducted. Relevant national legislation, policies, strategies, and international agreements ratified by South Africa were systematically reviewed, including environmental management, biodiversity conservation, climate change, and traditional knowledge protection instruments. Data were analysed thematically to assess policy coherence, implementation mechanisms, and alignment with climate adaptation objectives relevant to medicinal plant conservation. Results The analysis revealed that South Africa possesses a robust legislative foundation for biodiversity protection, particularly through the National Environmental Management: Biodiversity Act and associated regulations. However, climate change considerations are often addressed indirectly, with limited explicit integration of medicinal plant vulnerability, community-based adaptation, and Indigenous Knowledge Systems. Gaps were identified in policy coordination, implementation capacity, and monitoring of climate-driven impacts on medicinal plant populations. Conclusion Although South Africa’s policy and legislative frameworks provide a strong basis for biodiversity conservation, they inadequately address the specific and emerging risks posed by climate change to indigenous medicinal plant resources. The absence of targeted adaptation measures and weak integration of traditional knowledge limit the effectiveness of current responses. Recommendations The recommendation would be that climate change adaptation strategies explicitly incorporate indigenous medicinal plant conservation, strengthen community participation, and enhance cross-sectoral policy alignment. Integrating Indigenous Knowledge Systems with scientific monitoring can improve resilience and sustainable use of medicinal plant resources under changing climatic conditions.